Interstate war and food security: Implications from Russia's invasion of Ukraine - Nguyen, Trung T.; Timilsina, Raja R.; Sonobe, Tetsushi; Rahut, Dil B. (Frontiers in Sustainable Food Systems, 2023)
In this article, we review and shed light on the interlinkages between interstate war and food insecurity and discuss global policy actions needed to address the challenges of food insecurity due to interstate war. We conceptualize the interlinkages between these two issues with a focus on: (i) the most critical and direct cause of interstate war, namely geo (territorial) political conflict, and (ii) the mechanisms through which interstate war affects four different food security pillars, namely food availability, food access, food utilization, and food stability. We position that, if unsuccessfully addressed, geo (territorial) political conflicts will create a vicious cycle of violence and hunger. This position is illustrated by analysing recent Russia’s invasion of Ukraine. Herein a summary of the root and nature of the invasion and how it has affected global food security is presented, with a discussion on the potential considerations and solutions to avoid the cycle of violence and hunger.